Observation of the internal response of the kidney during compressive loading using ultrafast ultrasonography. Issue 10 (16th July 2015) - Helfenstein-Didier, C.; Tanter, M.; Gennisson, J.-L.; Beillas, P.
Abstract: A protocol based on ultrafast ultrasonography was developed to study the internal response of isolated perfused human ( n =3) and porcine ( n =11) kidneys subjected to loading at 0.003 m/s and 0.3 m/s respectively. Regional uniaxial strains were calculated based on natural target tracking. The effect of loading speed and regional differences could be statistically detected on the porcine specimens. However, despite the inhomogeneity of their anatomical structures, strains' responses appeared relatively homogeneous at 0.3 m/s in both porcine and human kidneys. Failure, identified as a sudden change on the ultrasonography movie, also appeared at similar compression levels for both species (38.3% of applied strain in average for human and 35.8% of applied strain in average for porcine).